Near-infrared plasmonic far-field nanofocusing effects with elongated depth of focus based on hybrid Au-dielectric-Ag subwavelength structures - Cao, Pengfei; Cheng, Lin; Zhang, Xiaoping; Huang, Xuelin; Jiang, Hongmei (Plasmonics, 2016)
In this paper, we propose a new far-field nanofocusing lens with elongated depth of focus (DOF) under near-infrared (NIR) wavelength. The surface plasmons can be excited by using the hybrid metal-insulator-metal (MIM) subwavelength structure under the NIR wavelength. The constructive interference of surface plasmons launched by the subwavelength MIM structure can form a nanoscale focus that is modulated by the novel metal grating from the near field to the far field. The numerical simulations demonstrated that a nanoscale focal spot (in plane focal area 0.177λ2) with elongated DOF (3.358λ) and long focal length (5.084λ) can be realized with reasonably designing parameters of the lens. By controlling the positions of the inner radii of each slit ring and the grating width, the focal length, focal spot, and DOF can be tuned easily. This design method, which can obtain the nanoscale focal spot and micron DOF in far field under NIR illumination, paved the road for utilizing the NIR plasmonic lens in superresolution optical microscopic imaging, optical trapping, biosensing, and complex wavefront/beam shaper.